Registration of synchronous geomagnetic pulsations and proton aurora during the substorm on March 1, 2017 - Varlamov Ilya (EDP Sciences, 2021)
Data of synchronous geomagnetic pulsations and proton aurora registrations were analyzed during the substorm on March 1, 2017 at Zhigansk (L=4.5, induction magnetometer), Maimaga (L=4, all-sky imager and Yakutsk (L = 3.3, induction magnetometer) stations, simultaneously with satellite measurement of EMIC waves. Ground-based registration of proton aurora is very difficult due to the fact that their intensity is much lower than the aurora intensity caused by precipitations of electrons, but in the event of substorm activity at the zenith of Maimaga station, a narrow (1 degree in latitude) proton arc was observed. Irregular pulsations of the diminishing periods (IPDPs) in the range of Pc1 geomagnetic pulsations associated with the injection of energetic protons were recorded simultaneously at Zhigansk and Yakutsk stations. This is the first report when STEVE (Strong Thermal Emission Velocity Enhancement) was observed in the course of a substorm with the onset at 12:45 UT after the decay of Pc1-associated proton arc. It is shown that the proton arc and geomagnetic pulsations are a consequence of ion-cyclotron instability in the area of the outer plasmasphere overlapping by energetic protons.